MARINE ENVIRONMENT A POTENTIAL SOURCE FOR CELLULOSE DEGRADING MICROORGANISM. - PRASAD M. P.; REKHA SETHI (International Journal of Pharma and Bio Sciences, 2014)
In the present study microorganisms have been isolated from coastal areas of southern parts of India using standard microbiological techniques. The isolates obtained were subjected to screening assay utilizing carboxy-methyl cellulose (CMC) as a substrate. CMC is a substrate for endoglucanase and so can be used as a test for endoglucanase and β-glucosidase activity. This assay is a good indicator of cellulolytic ability since endoglucanase is generally produced in larger titres by fungi than cellobiohydrolase. 92 bacterial isolates, 43 fungal and 11 actinomycetes were obtained out of which 42 bacteria, 16 fungi and 11 actinomycetes showed the ability to degrade cellulose. The screening assay clearly indicated that the isolates from the marine world could be of industrial importance for biodegradation of lignocellulosic biomass to release sugars which can be used as an alternative source of fuel such as ethanol. In addition the organisms could be used for the industrial production of celluloytic enzymes.